Study of Sensory, Nutritional and Storability of Variants of Instant panjiri Mixes - Alpana Sharma, Suman Kumar; S.P. Mishra (Indian Journal of Extension Education, 2018)
Panjiri, a traditional food product of Shahdol district and traditionally prepared from roasted wheat flour. Four variants of panjiri mixes incorporating different kinds of roasted legume dal flour viz., chickpea, green gram, soybean and field pea were prepared and evaluated on sensory, nutritional and storability parameters. Based upon the sensory evaluation, the optimized level of supplementation was found to be 10% supplementation of roasted legume dal flour in roasted wheat flour. Soybean blended mix showed better nutritional quality in comparison to other mixes. Fortification of mixes with 10% skimmed milk powder further enriched the products with higher contents of protein, calcium and phosphorus content. The prepared instant panjiri mixes were monitored for changes in moisture content, free fatty acids as well as sensory quality during storage and was found stable for 6 months at ambient conditions in polyethylene bags. The cost analysis of mixes showed that the cheapest products were based on soybean and fieldpea which had lower values in comparison to other products based on green gram and chickpea.